Knowledge management and “BRITA in PuBs” project - Kaklauskas, Artūras; Kanapeckiene, Loreta (Technological and Economic Development of Economy, 2005)
Driven by the rapid shift to information‐based products and business strategies the discipline of knowledge management is emerging as the inevitable next step toward productivity and competitiveness in modern business — and a major market opportunity for vendors of a variety of information‐related computer products. The proper analysis of the terminology of technologies that contribute to knowledge management solutions is the subject of this paper. This paper provides a high‐level overview of a number of key terms and concepts, describes the framework, provides examples of how to use it and explores a variety of potential application areas. The main comparative analysis of the definitions which were received from different terminology systems has been completed. It provides a framework for characterizing various tools (methods, practices and technologies) available to multiple criteria decision‐making in the dwelling‐housing procedure. In this paper we present a short description of “BRITA in PuBs” project. Article in Lithuanian. Žinių valdymas ir „BRITA in PuBs“ projektas Santrauka. Pateikta žinių valdymo ir žinių valdymo sistemų apibrėžimų analizė. Palyginti pateikta po 13 apibrežimų iš įvairių šaltinių. Išskirti žinių valdymo privalumai ir apibrėžtos žinių valdymo funkcijos. Remiantis atlikta žinių valdymo ir žinių valdymo sistemų analize, buvo sukurta gyvenamųjų pastatų atnaujinimo daugiakriterinė žiniomis grįsta sprendimų paramos sistema. Pateiktas projekto “BRITA in PuBs” trumpas aprašymas. Projektu “BRITA in PuBs” siekiama visuomeninių pastatų atnaujinimo sektoriaus dalyviams pademonstruoti, kaip galima inovatyviai ir efektyviai diegti pastatuose įvairius energijos taupymo sprendimus, kartu didinant šių pastatų kompleksinį kokybės lygš. Reikšminiai žodžiai: žinių valdymas, žinių valdymo sistemos, sprendimų paramos sistemos, ekspertinės sistemos. First Published Online: 21 Oct 2010